Economic Growth: Is it Green or not? An Application on OECD - Akarsu, Gülsüm; GÜMÜŞOĞLU, NEBİLE KORUCU (My University, 2021)
For climate change mitigation and considering other environmental impacts of traditional energy sources, countries have started to implement energy policies in favor of renewable energy sources. In this way, without any detrimental effect on economic growth, countries can decrease their fossil fuel consumption. However, there is a debate about the direction of causality between renewable energy consumption and economic growth as for the total energy-growth nexus. Moreover, in the literature, the studies focus only on the total or specific type of renewable energy consumption while analyzing the direction of causality. From this point of view, there is a gap in the literature in such a way that there is a need for a comprehensive analysis which compares the existence and direction of causality for different types of renewable energy sources and technologies. Therefore, the main aim of this study is to investigate renewable energy consumption and growth nexus. By using panel data on renewable electricity generation for OECD countries over the years from 2000 to 2016, the causality is tested for different technologies. Moreover, as the economic growth may not correctly measure the overall economic well-being, another measure for welfare is used. Therefore, the main motivation of this study is to include welfare in renewable energy and growth nexus in which different type of technologies for renewable energy are considered. The results for both economic growth and welfare measure show that the existence and directi highly differs among the different technologies. Therefore, technology specific policies should be implemented in order to stimulate the renewable energy investments and consumption.
Keywords: Renewable energy consumption; Green growth; Panel data; Causality; Welfare